Comparative Analysis of Apology Strategies Utterances between Male and Female English Department Students - Debby Handayani Pratiwi; Hamzah Hamzah (Universitas Negeri Padang, 2022)
This study aims to compare the differences and the similarities between male and female English department students in using apology strategies. The are five types of apology strategies according to Olshtain and Cohen (1983); 1) expression of apology, 2)offer of repair, 3)explanation of account, 4)acknowledgement responsibility for offense, and 5)promise of forbearence.. The method used in this research was a descriptive-qualitative. The data samples were taken from English Department students at Padang State University. Data was retrieved using a questionnaire form. The data were collected in form of sentences which were the utterances of the participant. The results of the study showed that male and female have some differences and similarities in using apology strategies. Both female and male students use all five of types of apology strategies. The most preferred type of strategy by both female and female was expression of apology and the least preferable was promise forbearance. The result reveals that male and female students tend to use similar strategies in making apology.